The Swiftlet Nest Business of Gua Sibarasok: A Historical Study in Pasar II Singkuang Village, Muara Batang Gadis District, Mandailing Natal Regency (1989-2020) - Amliansyah Amliansyah; Ulfah Nury Batubara; Deka Maita Sandi; Henry Harahap (Tarikhuna: Journal of History and History Education, 2025)
This study investigates the history of the swiftlet nest business at Gua Sibarasok in Pasar II Singkuang Village, Muara Batang Gadis District, Mandailing Natal Regency. It aims to describe the historical background of the business's emergence and analyze its socio-economic impact on the community. This qualitative study employs a historical method encompassing four stages: heuristic, source criticism, interpretation, and historiography. Findings reveal that the swiftlet nest business at Gua Sibarasok originated from the cave's discovery in 1989. Initially, it was privately managed. However, in 1990, the Singkuang Village community claimed rights to Gua Sibarasok, establishing it as a community-owned enterprise with management subsequently transferred to PT Mujur Timber. In 1993, the Singkuang Village community formed KUD Singkuang to manage Sibarasok Cave. Yet, in 1999, KUD Singkuang handed over management to PT Anugerah Langkat Makmur, which continues to manage it today. The presence of Sibarasok Cave, containing high-quality swiftlet nests, has significantly contributed to improving the economy and generating employment for the residents of Pasar II Singkuang Village. Despite these positive contributions, the swiftlet nest business at Sibarasok Cave has also led to negative impacts, including various community conflicts and environmental degradation.